Robert Wickliffe Woolley papers - Woolley, Robert Wickliffe, 1871-1958.
Correspondence, memoranda, speeches, unpublished autobiography, reports, articles, subject files, financial records, family papers, genealogical material, clippings, printed matter, memorabilia, photographs, and other papers pertaining chiefly to Woolley's work organizing party publicity for the Democratic political campaigns of 1912, 1916, and 1920; and to his work as a member of the U.S. Interstate Commerce Commission, 1917-1921. Subjects include national political affairs, regulation of railroads during and after World War I, fuel economy, and U.S. Senate's Committee on Interstate Commerce inquiries. Correspondents include Alben William Barkley, Louis Dembitz Brandeis, Desha Breckinridge, James M. Cox, Josephus Daniels, Edward Mandell House, W.G. McAdoo, George Foster Peabody, Franklin D. Roosevelt, Daniel C. Roper, Harry S. Truman, Joseph P. Tumulty, and Woodrow Wilson.
In part, photostats reproduced from originals in private hands.
Private
Journalist, politician, and public official.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Barkley, Alben William, -- 1877-1956 -- Correspondence; Brandeis, Louis Dembitz, -- 1856-1941 -- Correspondence; Breckinridge, Desha, -- 1867-1935 -- Correspondence; Cox, James M. -- 1870-1957 -- Correspondence; Daniels, Josephus, -- 1862-1948 -- Correspondence; House, Edward Mandell, -- 1858-1938 -- Correspondence; McAdoo, W. G. -- 1863-1941 -- Correspondence; Peabody, George Foster, -- 1852-1938 -- Correspondence; Roosevelt, Franklin D. -- 1882-1945 -- Correspondence; Roper, Daniel C. -- 1867-1943 -- Correspondence; Truman, Harry S., -- 1884-1972 -- Correspondence; Tumulty, Joseph P. -- 1879-1954 -- Correspondence; Wilson, Woodrow, -- 1856-1924 -- Correspondence; Woolley family; United States. -- Congress. -- Senate. -- Committee on Interstate Commerce; United States. -- Interstate Commerce Commission; Democratic Party (U.S.); Elections -- United States -- 1912.; Elections -- United States -- 1916.; Elections -- United States -- 1920.; Energy policy -- United States; Fuel consumption; Interstate commerce -- United States; Railroads -- United States; Railroads and state -- United States; World War, 1914-1918 -- Transportation -- United States; United States -- Commerce; United States -- Politics and government -- 1901-1953.; Journalists; Politicians; Public officials